2015
DOI: 10.1007/s00216-015-8539-z
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational algorithms for quantitative crystallographic analyses of hydroxyapatite-based biomaterials: II, application to decayed human teeth

Abstract: A systematic investigation, based on highly spectrally resolved Raman spectroscopy, was undertaken to research the efficacy of vibrational assessments in locating chemical and crystallographic fingerprints for the characterization of dental caries and the early detection of non-cavitated carious lesions. Raman results published by other authors have indicated possible approaches for this method. However, they conspicuously lacked physical insight at the molecular scale and, thus, the rigor necessary to prove t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Hence, we used values showing the ratio of fluorescence intensity of calculus to the intensity of the HA Raman band, as previous studies reported that the amount of calculus present was in proportion to fluorescence intensity [ 22 ] and the HA Raman band provided quantitative information regarding minerals in biomaterials such as bones [ 16 ] and teeth [ 20 ]. In our study, the corrected spectrum values were normalized to the HA Raman band intensity at 960 cm −1 to produce quantitative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we used values showing the ratio of fluorescence intensity of calculus to the intensity of the HA Raman band, as previous studies reported that the amount of calculus present was in proportion to fluorescence intensity [ 22 ] and the HA Raman band provided quantitative information regarding minerals in biomaterials such as bones [ 16 ] and teeth [ 20 ]. In our study, the corrected spectrum values were normalized to the HA Raman band intensity at 960 cm −1 to produce quantitative results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been applied to the pathology of hard tissues including bones and teeth, by obtaining Raman spectra of hydroxyapatite (HA) and organic components such as proteins [ 16 18 ]. It has also been reported that detailed Raman spectral analysis of HA was highly useful for assessments of decayed teeth [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [1,6,7], we have systematically and quantitatively monitored the evolution of tooth enamel demineralization according to the chemical formula, Ca 5-y (HPO 4 ) y (PO 4 ) 3−y (OH) 1−y (H 2 O) y . This is a generally valid chemical representation of the enamel apatite structure in the presence of a fraction y of Ca vacancies.…”
Section: Linking the Raman Spectrum To The Severity Of The Cavitated mentioning
confidence: 99%
“…Evaluations of crystallinity, residual stress analyses, and chemical assessments of molecular structures can thus be performed without contact, damage, or radiation exposure. Since Raman spectroscopy allows analysis at the molecular level without requiring fluorescent probes, fixation, or other types of manipulation, it has recently received attention for its potential applications in several fields of medical science, including dentistry [1]. Various methods of dental analysis using Raman spectroscopy have recently been reported, such as the detection of trace elements in the enamel [2] and the detection of dentin formation in the dental pulp tissue [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation